The Influence Of Snack Portion Size Design On Teens And Young Adults Consumption - Miki Tjandra; Elizabeth Wianto; Monica Hartanti; Hendra Setiawan; Beverly Clara (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
This research is motivated by the trend of snacks with a salty or sweet taste which have become part of people's lifestyles, especially among teenagers and young adults. Snacks portion that exceeds the serving size has an unfavorable impact on the body's calorie intake. This study aims to analyze the effect of the size of the snack packaging portion in the form of one serving (individual pack) and family portion (family pack), on the eating patterns of teens and young adults. The population in this study were active students from several universities in Bandung, Indonesia. Data collection was done by distributing questionnaires to respondents. The study was conducted using descriptive statistical calculations and inferential statistics, namely the comparison between respondents' preferences for the choice of snack packaging that is packaged according to the serving sizes and packaged in larger sizes. Teenagers and young adults choose snacks with larger packages, both from the salty and sweet snack groups. Larger packaging sizes dominate purchasing decisions. They consume more snacks if served in larger packages. Consumers prefer large packaging which is more economical because small packaging does not have a visible added value. Individual packaging is only effective when carried or when you want to eat less snack. Based on the conclusions, further research that focuses on increasing the value of single-serving packages, how to pack family-sized snacks (family packs) to increase awareness of snack portions, or how other efforts can be made to change the behavior of eating excess snack portions can be further explored.